NON-GOVERNMENTAL ORGANIZATION FINANCIAL ACCOUNTABILITY: PERSPECTIVES ON MOTIVES FOR ACTION AND SOCIAL INTERACTION - Anah Nurjanah; M. Irfan Tarmizi; Eva Herianti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study intends to analyze and describe the sociality experiences of employees of the Finance department, Director, Deputy Director and Manager of Research and Knowledge in managing institutions in order to achieve the principle of accountability through social interaction and the motives of their actions. This research method uses qualitative proximity to the phenomenological method of Schutz's sociology. Data collection techniques are carried out by interviews, observations and documentation. Interviews were conducted with six employees who worked at The Prakarsa. Observations are made unstructured. Documentation in the form of field notes, photos, information boards in each division containing financial reports and project budgets. Data analysis combines interpretive phenomenological analysis (IPA) techniques with Schütz's phenomenology. The data analysis stage includes coding (interpretation, condensation and categorization of themes) and analysis. The interpretation of the results uses the Schutz concept of sociality, namely social interaction and the motives of actions. The results of the analysis show that: first, the accountability process in financial management is carried out by employees. Employees who are actually individuals who position themselves as related actors in a social process in the world of work. In other words, this indicate that employees in achieving accountability for financial management through sociality in the motives of actions and social interactions. Second, the motives for actions carried out with an honest attitude in carrying out work, prudent in acting, innovative in work, facing internal and external challenges by presenting reports transparent finance, the importance of finding donors and submitting financial reports both to the public and internally. Meanwhile, social interaction is carried out with other parts and interested third parties. Because basically accountability establishes a connection to all parties related to the organization.